The development of quick, robust, quantitative phenotypic assays for describing the host–nonhost landscape to stripe rust - Dawson, Andrew M.; Bettgenhaeuser, Jan; Gardiner, Matthew; Green, Phon; Hernández-Pinzón, Inmaculada; Hubbard, Amelia; Moscou, Matthew J. (Frontiers in Plant Science, 2015)
Nonhost resistance is often conceptualized as a qualitative separation from host resistance. Classification into these two states is generally facile, as they fail to fully describe the range of states that exist in the transition from host to nonhost. This poses a problem when studying pathosystems that cannot be classified as either host or nonhost due to their intermediate status relative to these two extremes. In this study, we investigate the efficacy of the Poaceae-stripe rust (Puccinia striiformis Westend.) interaction for describing the host–nonhost landscape. First, using barley (Hordeum vulgare L.) and Brachypodium distachyon (L.) P. Beauv. We observed that macroscopic symptoms of chlorosis and leaf browning were associated with hyphal colonization by P. striiformis f. sp. tritici, respectively. This prompted us to adapt a protocol for visualizing fungal structures into a phenotypic assay that estimates the percent of leaf colonized. Use of this assay in intermediate host and intermediate nonhost systems found the frequency of infection decreases with evolutionary divergence from the host species. Similarly, we observed that the pathogen’s ability to complete its life cycle decreased faster than its ability to colonize leaf tissue, with no incidence of pustules observed in the intermediate nonhost system and significantly reduced pustule formation in the intermediate host system as compared to the host system, barley-P. striiformis f. sp. hordei. By leveraging the stripe rust pathosystem in conjunction with macroscopic and microscopic phenotypic assays, we now hope to dissect the genetic architecture of intermediate host and intermediate nonhost resistance using structured populations in barley and B. distachyon.